ECCENTRIC TRAINING IMPROVES TENDON BIOMECHANICAL PROPERTIES: A RAT MODEL. Issue 7 (11th March 2014) - Kaux, JF; Drion, P; Libertiaux, V; Colige, A; Hoffmann, A; Nusgens, B; Forthomme, B; Le Goff, C; Franzen, R; Rickert, M; Crielaard, JM; Croisier, JL
Abstract : Background: Even if eccentric exercises appear favourable in primary prevention of tendons lesions and, especially, in secondary prevention after tendinopathy, the biomechanical changes to the tissue are not yet clear. Objective: We aimed to better define the biomechanical changes that affect healthy tendon after eccentric and concentric training. Design: Randomised controlled trial. Setting: Animal study. Participants: 18 Sprague-Dawley rats of 2 months. Interventions: The 6 rats in the control group (U) were not subjected to physical exercise. The 12 remaining rats (6 in each group) ran on a treadmill set at a +15° incline for concentric training (C) or a −15° incline for eccentric training (E), at a speed of 17 m/min for 1 h, three times per week for 5 weeks. Main outcome measurements: The tricipital, patellar and Achilles tendons were subsequently removed to perform a traction test until rupture, and a histological analysis was performed. Results: There was a significant improvement in the rupture force of the patellar and tricipital tendons between the U and E groups. The tricipital tendons in the control group presented a significantly smaller cross-section than the E- and C-trained groups, but none between E and C groups. No significant difference was observed for the mechanical stress at rupture per surface unit between the three groups for all three tendons. However, a tendency towards improvement these values was observed between the trained and the U groups for the patellar tendon. Histological studies demonstrated the tendency of the development of a greater number of blood vessels and a larger quantity of collagen in the eccentric group. Conclusions: The mechanical properties of tendons in rats improve after specific training, especially following eccentric training. Our results partly explained how mechanical loading, especially in eccentric mode, could improve the tendon structure and perhaps prevent to tendon pathologies.